LATE JURASSIC CLIMATES, VEGETATION, AND DINOSAUR DISTRIBUTIONS - McAllister Rees P.; Noto C.R.; Parrish J.M.; Parrish J.T. (My University, 2004)
The Jurassic and Cretaceous are considered to have been warmer than today on the basis of various climate data and model studies. Here, we use the available global record of climate-sensitive sediments, plants, and dinosaurs to infer broadscale geographic patterns for the Late Jurassic. These provide a context for our more detailed accounts of the Morrison and Tendaguru Formations in North America and East Africa. At the global scale, evaporites predominated in low latitudes and coals in mid- to high latitudes. We ascribe these variations to a transition from drier to wetter conditions between the equator and poles. Plant diversity was lowest in equatorial regions, increasing to a maximum in midlatitudes and then decreasing toward the poles. Most dinosaur remains are known from low-latitude to marginally midlatitude regions where plant fossils are generally sparse and evaporites common. Conversely, few dinosaur remains are known from mid- to high latitudes, which have higher floral diversities and abundant coals. Hence, there is an obvious geographic mismatch between known dinosaur distributions and their primary food source. This may be due to taphonomic bias, indicating that most dinosaur discoveries provide only a small window on the diversity and lifestyles of this group. On the basis of our global- and local-scale studies, we suggest that dinosaur preservation was favored in environments toward the drier end of the climate spectrum, where savannas rather than forests predominated. A holistic approach, incorporating climate and vegetation as well as geography, is required to better understand patterns of dinosaur ecology and evolution.
Keywords: Jurassic; Mesozoic::Jurassic; Мезозой::Юрская